2020
DOI: 10.26717/bjstr.2020.31.005032
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Elite Athletes and Essential Hypertension Patients for Angiotensin-Converting Enzyme (ACE) I/D and ACE G2350A Gene Polymorphisms

Abstract: Objective: Angiotensin-converting enzyme (ACE) gene produces an ACE protein which is the key component of the renin-angiotensin system and contains several polymorphisms which affects the physical performance that is significantly important for athletes. Insertion/deletion (I/D) and G2350A polymorphisms which have one of the most powerful influences in the ACE gene is known to regulate cardiovascular mechanisms by taking a role in angiotensin-system. Methods:The present study aimed to investigate the genetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…This gene was shown to include 26 exons as well as 25 introns and encodes a protein containing 1,306 amino acid. Previous records of National Center for Biotechnology Information (NCBI) had shown that ACE gene had more than 160 polymorphisms (mainly single nucleotide polymorphisms (SNP) 16 . Within the circulation, ACE G2350A gene (one of the ACE genes) had demonstrated a significant role in the determination of ACE level 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This gene was shown to include 26 exons as well as 25 introns and encodes a protein containing 1,306 amino acid. Previous records of National Center for Biotechnology Information (NCBI) had shown that ACE gene had more than 160 polymorphisms (mainly single nucleotide polymorphisms (SNP) 16 . Within the circulation, ACE G2350A gene (one of the ACE genes) had demonstrated a significant role in the determination of ACE level 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Other polymorphism is the insertion/deletion (I/D) one which represents the most widely studied ACE polymorphism. It is characterized by the presence of a 287 bp Alu repeat sequence (insertion) or absence (deletion) in intron 16 . This produces three genotypes (wild I/I homozygous, heterozygous I/D heterozygote, and mutant homozygous D/D) 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%